Using the Methods of Teaching in the Professional Training of Future Translators and Interpreters at the Universities of Great Britain - Sergieyeva, Oksana (Pedagogical Discourse, 2018)
The article deals with the main methods of teaching for the future translators and interpreters in the British professional education. The author examined that the methods which provide for the organization of active interaction between teachers and students and between by the students themselves. The role of the teacher in creating learning conditions of translation and interpreting situation is examined. The author concludes about effectiveness of the analysed methods of teaching for translators and interpreters education and the possibility of their implementation in educational system of Ukraine.